2012
DOI: 10.1111/jam.12055
|View full text |Cite
|
Sign up to set email alerts
|

A subset of histamine receptor ligands improve thermotolerance of the yeast Saccharomyces cerevisiae

Abstract: Aims: Histamine interacts with the stress response in eukaryotes. This study investigated the effects of antihistamines on the heat shock (HS) response in yeast, thereby exploring their functions in a well-established histamine receptor (H x R)-free model. Methods and Results: Stress response was evaluated by determining growth and viability of postlogarithmic phase grown yeast cultures after HS at 53°C for 30 min. The effects of H x R ligands were investigated following short-and long-term administration. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…S4). The fact that flunarizine was identified in an assay based on S. cerevisiae yeast cells that lack known homologues of histamine receptors [48] is an additional argument indicating that the H1 receptor is not involved in the anti-prion effect of the drug tested. Finally, since 5 out of the 13 inactive compounds tested also bind to H1 receptor, we concluded that H1 receptor is unlikely to be involved in PrP Sc clearance.…”
Section: Flunarizine and Its Structural Analogs Are Pfar Inhibitorsmentioning
confidence: 99%
“…S4). The fact that flunarizine was identified in an assay based on S. cerevisiae yeast cells that lack known homologues of histamine receptors [48] is an additional argument indicating that the H1 receptor is not involved in the anti-prion effect of the drug tested. Finally, since 5 out of the 13 inactive compounds tested also bind to H1 receptor, we concluded that H1 receptor is unlikely to be involved in PrP Sc clearance.…”
Section: Flunarizine and Its Structural Analogs Are Pfar Inhibitorsmentioning
confidence: 99%
“…The CSR to adverse environmental/ microenvironmental conditions is governed by evolutionary conserved endogenous multicomponent processes, including heat shock protein (Hsp) expression and ion homeostasis (Święciło 2016). Physical, chemical, or physiological stimuli, such as heat, drugs, and hormones trigger and/or modulate CSR (Delitheos et al 2010;Papamichael et al 2006;Papamichael et al 2013). The evolutionary conservation of the basic physiological and biochemical, cellular, and molecular mechanisms between yeasts and higher eukaryotes made the yeast an established experimental model for the pharmacological inves-tigation of the CSR and the adaptive and protective mechanisms underlying drug resistance (Verghese et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Η ισταμίνη ασκεί τις δράσεις της μέσω σύνδεσης με τους υποδοχείς Η 1 -Η 4 (Εικόνα 1.17) (Bongers et al, 2010• Panula et al, 2015, αν και έχουν παρατηρηθεί δράσεις της ισταμίνης ανεξάρτητες των υποδοχέων σε διάφορα συστήματα και οργανισμούς (Walther et al, 2011• Kyriakidis et al, 2012• Kyriakidis and Tiligada, 2013• Papamichael et al, 2013.…”
Section: υποδοχείς ισταμίνης και αντισταμινικά φάρμακαunclassified